2009
DOI: 10.1017/s0263034609990310
|View full text |Cite
|
Sign up to set email alerts
|

Ramp wave loading experiments driven by heavy ion beams: A feasibility study

Abstract: A new design for heavy-ion beam driven ramp wave loading experiments is suggested and analyzed. The proposed setup utilizes the long stopping ranges and the variable focal spot geometry of the high-energy uranium beams available at the GSI Helmholtzzentrum für Schwerionenforschung and Facility for Antiproton and Ion Research accelerator centers in Darmstadt, Germany. The release wave created by ion beams can be utilized to create a planar ramp loading of various samples. In such experiments, the predicted high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Theoretical work has shown that an intense heavy ion beam can be efficiently employed to isentropically implode a sample material like hydrogen or water that will generate physical conditions which are expected to exist in the interiors of the giant planets in our solar systems as well as in exoplanets [9][10][11][12]. An experiment based on this scheme, named LAPLAS (Laboratory Planetary Sciences) has been proposed to study planetary physics at FAIR [9].…”
Section: Planetary Physics Research At Fairmentioning
confidence: 99%
“…Theoretical work has shown that an intense heavy ion beam can be efficiently employed to isentropically implode a sample material like hydrogen or water that will generate physical conditions which are expected to exist in the interiors of the giant planets in our solar systems as well as in exoplanets [9][10][11][12]. An experiment based on this scheme, named LAPLAS (Laboratory Planetary Sciences) has been proposed to study planetary physics at FAIR [9].…”
Section: Planetary Physics Research At Fairmentioning
confidence: 99%
“…However, the characterization of the states of matter that are created assumes often local thermodynamic equilibrium. This is clearly fulfilled for slow energy deposition as in shockexperiments driven by high explosives [1] or ion beams [2], during isentropic compression of materials [3,4], or heating by particle beams [5]. On the other hand, laser driven shocks and laser heating can be sufficiently fast to create states that significantly differ from equilibrium.…”
Section: Introductionmentioning
confidence: 99%